Ovarian Diffuse Large B-cell Lymphoma Initially Suspected Dysgerminoma Managed by Laparoscopic Staging Surgery - Pei- Chen Li; Pei Qi Lim; Yung- Hsiang Hsu; Dah- Ching Ding (Wolters Kluwer Medknow Publications, 2020)
Ovarian diffuse large B-cell lymphoma (DLBCL) is rare. DLBCL is a complex type of lymphoma. The ovarian DLBCL usually harbor a favorable prognosis. We report a case of ovarian DLBCL that presented as an ovarian mass with lower abdominal pain and was managed using laparoscopic staging surgery. A 29-year-old female (gravida 2, para 0, abortion 2) with a history of polycystic ovarian syndrome with irregular medication control visited our clinic due to lower abdominal pain. Transvaginal ultrasound revealed a heterogeneous, septated mass over the left adnexa with a diameter of approximately 6 cm × 8 cm. The tumor marker CA 19-9 was elevated (65.77 IU/mL); CA125 and carcinoembryonic antigen were not elevated. Laparoscopic surgery with left salpingo-oophorectomy was first performed. Frozen section indicated dysgerminoma. Then, we continued staging surgery through bilateral pelvic lymph node dissection, para-aortic lymph node dissection, omentectomy, right ovary and peritoneum biopsy, and washing cytology. Ovarian tumor and para-aortic lymph nodes were positive for lymphoma. The tumor cells were positive staining for CD20, CD5, ki67, BCL-6, and MUM-1, which was associated with DLBCL. The patient was then consulted for oocyte preservation and referred to hematology for further chemotherapy. In conclusion, an ovarian lymphoma is a rare event. The presence of an enlarged ovarian tumor should raise the suspicion of ovarian lymphoma. To differentiate ovarian lymphoma from dysgerminoma, immunohistochemistry is useful. Fertility preservation should be considered before chemotherapy. Ovarian tissue or oocyte preservation or gonadotropin-releasing hormone agonist injection before chemotherapy can be performed for fertility preservation.